Drivers of Live-Stream Shopping Intention: Case Study of Shopee Malaysia - Hala Najwan Sabeh; Thiam Yong Kuek; Malini Lim Tamil Chelvan; Marsya Zahirah Muhamad Zahiri; Mazuin Izati Zainul Aalam; Si Jia Min; Zanyar Abdulbast Qadr; Diyar Ghufran Salim Sam; Daisy Mui Hung Kee (Advances in Global Economics and Business Journal, 2026)
The rapid growth of live-stream shopping has changed consumer purchasing behavior. In Malaysia, Shopee Live has become a popular platform for consumers to engage with streamers in real time. This study aims to investigate the key factors influencing consumer’s intentions in live-stream shopping on Shopee Malaysia. We want to find out the impact of perceived enjoyment, trust in streamers, perceived utility, and self-presentation on live-stream shopping intention. A quantitative research method will be used, and data will be collected through a survey questionnaire distributed via Google Forms from 153 Shopee Live users in Malaysia. Our findings indicates that consumers live-stream shopping intentions in Shopee Live are driven primarily by self-presentation, followed by perceived utility and trust in the streamer, while perceived enjoyment does not significant influenced. This study contributes to a better understanding of consumer behavior in live-stream commerce and to help Shopee Malaysia develop more effective live-streaming strategies that strengthen consumer’s shopping intentions in the long term.